A multipoint problem with multiple nodes for linear hyperbolic equations - Beresnevich, V. V.; Bernik, V. I.; Vasylyshyn, P. B.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish conditions for the unique solvability of a multipoint (with respect to the time coordinate) problem with multiple nodes for linear hyperbolic equations with constant coefficients in the class of functions periodic in the space variable. We prove metric statements concerning lower bounds of small denominators that appear in the course of construction of a solution of the problem.